Pengaruh Kesabaran terhadap Kecemasan pada Perempuan Dewasa di Kecamatan Kiaracondong - Kusumaningtyas Retno Palupi; Umar Yusuf Supriatna (Bandung Conference Series: Psychology Science, 2022)
Abstract. The current development of the COVID-19 pandemic in Indonesia has an impact on people's mental health. Anxiety is one of the mental health disorders experienced by society today. The daily pressures make it difficult for adult women to control their worries about the current COVID-19 pandemic situation. The level of individual vulnerability to anxiety is influenced by psychological conditions such as patience. This study was conducted to determine the effect of patience on anxiety during the pandemic in adult women in Kiaracondong District. The subjects of this study were 344 adult women aged 18-40 years in Kiaracondong District. In this study, using a measuring tool for patience from the Yusuf concept (2021) with 48 items and using the Hamilton Anxiety Rating Scale (HARS) measuring instrument with 14 items. This research was conducted using a simple linear regression test. The results showed that the R square value was 0.316. This means that patience affects anxiety during the pandemic in adult women in Kiaracondong District by 31.6%. Abstrak. Perkembangan pandemi COVID-19 di Indonesia saat ini berdampak pada kesehatan mental masyarakat. Kecemasan merupakan salah satu gangguan kesehatan mental yang dialami oleh masyarakat saat ini. Tekanan sehari-hari menyebabkan perempuan dewasa mengalami kesulitan untuk mengontrol kekhawatiran terhadap situasi pandemi COVID-19 yang terjadi saat ini. Tinggi rendahnya kerentanan individu mengalami kecemasan salah satunya dipengaruhi oleh kondisi psikologis seperti kesabaran. Penelitian ini dilakukan untuk mengetahui pengaruh kesabaran terhadap kecemasan masa pandemi pada perempuan dewasa di Kecamatan Kiaracondong. Subjek penelitian ini merupakan 344 perempuan dewasa berusia 18-40 tahun di Kecamatan Kiaracondong. Pada penelitian ini menggunakan alat ukur kesabaran dari konsep Yusuf (2021) dengan 48 item dan menggunakan alat ukur Hamilton Anxiety Rating Scale (HARS) dengan 14 item. Penelitian ini dilakukan dengan menggunakan uji regresi linier sederhana. Hasil penelitian menunjukkan nilai R square 0,316. Artinya kesabaran mempengaruhi kecemasan masa pandemi pada perempuan dewasa di Kecamatan Kiaracondong sebesar 31,6%.